The impact of providing a continuum of care in the throughcare and aftercare process - Caroline Chittleburgh (Scottish Journal of Residential Child Care)
This paper is based on the findings of a piece of practitioner research. The research examined the impact of providing an aftercare service to young people supported by one voluntary organisation as they make the transition from being 'looked after and accommodated' to living independently in the community. This voluntary organisation has supported children and young people since 1733. It set up an aftercare service in 2004 in response to concerns about the transition of young people into the community. Research in the area of throughcare and aftercare has highlighted major problems (Dixon and Stein, 2002; 2005; Stein, 2006; Elsley et al., 2007). In response to such findings, regulations and guidance were published, outlining responsibilities for supporting young people leaving care (Scottish Executive, 2004). The Regulations and Guidance includes duties to assess and review a young person's aftercare needs and to establish clear plans called pathways. In addition to this, reports and guidelines on best practice have been developed which offer support to practitioners (Scottish Throughcare and Aftercare Forum, 2006; Scottish Commissioner for Children and Young People [SCCYPJ, 2008). The aftercare service on which this paper is based was set up in 2004. The principles behind the service were based on a series of factors identified by young people as being important to them when they were in transition.